Process modelling and simulation of degradation of 2-amino-2-methyl-1-propanol (AMP) capture plant - Osagie, Ebuwa; Biliyok, Chechet; Di Lorenzo, Giuseppina; Manovic, Vasilije (Elsevier, 2017)
The presence of contaminants in the flue gas stream such as O2, CO2, SOX, and NOX can cause solvent degradation in solvent-based CO2 capture processes. In this study, the major degradation products reactions of the AMP-based CO2 capture process has been included in the Aspen Plus® V8.4 simulation software using equilibrium reactions. Assessing the solvent degradation, solvent concentration and flowrate were varied. The results showed that the AMP losses reduced by decreasing solvent flowrate and concentration. Largest energy savings are observed when increasing concentration up to 34 wt. %.
Keywords: Degradation; 2-amino-2-methyl-1-propanol (AMP); CO2 capture plant; Process modelling and simulation